GmWRKY45 Enhances Tolerance to Phosphate Starvation and Salt Stress, and Changes Fertility in Transgenic Arabidopsis - Li, Cheng; Liu, Xinyi; Ruan, Hui; Zhang, Jingyao; Xie, Fengbin; Gai, Junyi; Yang, Shouping (Frontiers in Plant Science, 2020)
WRKY protein is a unique transcription factor (TF) of plants and plays an important role in the physiological processes of various stress responses and development. In this research, we obtained a WRKY TF gene from soybean by homologous cloning, and named it GmWRKY45. GmWRKY45 is a nuclear protein containing a highly conserved WRKY domain and a C2H2 zinc finger structure, and mainly expressed in roots, flowers and pods. The quantitative reverse transcription–PCR showed that GmWRKY45 was induced by phosphorus starvation and salt stress. As compared with the wild type (WT), overexpression of GmWRKY45 in Arabidopsis increased the adaptability of transgenic lines to phosphate starvation, which may be related to the enhancement of lateral root development. The content of phosphorus and dry and fresh weight of Arabidopsis GmWRKY45-overexpressing plants were higher than those of WT under both Pi-sufficient and Pi-deficient medium. Meantime, the expression of PSI genes was affected in transgenic Arabidopsis. Furthermore, GmWRKY45 improved the salinity tolerance and changes fertility in transgenic Arabidopsis. Under salt stress, we found the survival rate and soluble sugar content of transgenic Arabidopsis was significantly higher than that of WT plants. In a normal soil pot experiment, the transgenic Arabidopsis produced shorter silique and less seed bearing than WT because of partial abortion of pollen. However, the seeds of Arabidopsis with overexpression of GmWRKY45 were larger than WT plants. The overall results show that GmWRKY45 was not only involved in plant response to abiotic stress but also related to plant fertility, suggest that GmWRKY45 had an elaborate regulatory system in plants.